Déstabiliser la binarité en archéologie : le cas des tombes 137 et 260 de la nécropole mérovingienne de Bossut-Gottechain - Laura Mary (Frontière·s)
Sex is a 'biological, unchanging and universal category'. Gender is a 'socially constructed system that hierarchically categorizes the sexes'. Since the first studies in gender archaeology from the 1980s, recent research has invited us to question these definitions, to stop considering sex as a fixed entity and to go beyond the binary model of sex and gender. These reflections, however, still struggle to find their way into Merovingian archaeology. Starting with two specific graves in the necropolis of Bossut-Gottechain (Belgium), this article aims to question the binary categorization of sex and gender in archaeology.